Ethosuximide associated drug reaction with eosinophilia and systemic symptoms syndrome masqueraded as adenovirus infection - Abraham, Emi R.; Varghese, Serena M.; Chandran, Gopika M.; Varghese, Dinu (International Journal of Basic & Clinical Pharmacology, 2025)
Drug Reaction with Eosinophilia and Systemic Symptoms (DRESS) syndrome is a serious adverse reaction due to drugs. Due to the rarity of this condition particularly in children, DRESS can be often misdiagnosed. An 8-year-old boy was referred to our paediatrics department with the complaints of persisting fever and rashes. He was tested positive for Adenovirus infection and was provisionally diagnosed with urticaria due to viral infection, for which he was started with antiviral and antipyretics. The child was also recently diagnosed with Myoclonic Absence Epilepsy and was started on syrup Ethosuximide. Despite being treated with antiviral and antipyretics his fever spikes were consistent with itchy rashes. Multidisciplinary medical consultations were done to finally rule out DRESS associated with Ethosuximde and the drug was stopped. The child showed significant improvement from the next day with no further episodes of fever spike. Hence, we present this case to provide an alert for the need of early differential diagnosis of DRESS syndrome in case of concomitant viral infection.